Effect of Zinc concentration in CdS thin films deposited in complexing agent by chemical bath deposition: structural, optical, morphological and topographical studies. (12th February 2020) - Settu, P; Gobi, G; Baskaran, P; Manikandan, K
Abstract: ZnCdS thin films were prepared by varying the concentration of Zinc (Zn) in the presence of complexing agent, tri-ethanol amine (TEA) and deposited on a glass substrate by chemical bath deposition (CBD) method. The influence of Zn on structural, optical and morphological properties of ZnCdS thin films was studied. From the x-ray diffraction pattern (XRD), the hexagonal structure of ZnCdS thin films was confirmed with an average size of the crystallite (30–36 nm). The optical properties of ZnCdS thin film were investigated using UV–visible absorption and photoluminescence spectral analysis (UV-Vis and PL). The optical studies of thin films indicated that the band gap increased from 1.85 eV to 2.81 eV with increasing the concentration of Zn. Transmission spectra showed a blue shift with increasing the concentration of Zn. The microstructure and morphology of ZnCdS thin films were studied by scanning electron microscope (SEM). The average (Ra) and RMS roughness was calculated by atomic force microscope (AFM). From the results, the nano ZnCdS thin films prepared using various concentrations of Zn could be useful for optoelectronic and device applications.